In memoriam. Marco Aurelio Denegri Santagadea (1938-2018) - Godenzi Alegre, Jorge Luis (2018)
Eighty years were enough for this lanky intellectual to be a fervent entertainer in televised cultural gatherings. He was a music lover, article writer, vallejólogo, historiographer, misanthrope, lexicographer, sexologist, bibliographer, magazine founder, Peruvian cajón scholar, specialist in gallistics and founder of the Asociación de Estudios Humanísticos (Association of Humanistic Studies).